Unravelling effects of project complexity on project success and project management success: a meta-analytic review - Hu, Zhibin; Wu, Guangdong; Zheng, Junwei; Zhao, Xianbo; Zuo, Jian (Journal of Civil Engineering and Management, 2023)
Construction project complexity can be daunting, so both academics and practitioners have been looking for guidance. Previous studies have attempted to reconcile the inconsistencies and complexities in the relationships among project complexity, project success, and project management success. However, such research has failed to establish these clear relationships. Accordingly, the approach of systematic review and meta-analysis is applied in this study to investigate and compare how different project complexity affects project success and project management success by selecting 22 articles and 77 effect sizes. The results indicate that integrational complexity significantly positively affects project success, whereas it is not significantly negatively associated with project management success. Within a technical-organizational-environmental (TOE) framework, effects of organizational, environmental, and technical complexity on project success and project management success are also discussed here. A possible moderator (the national/regional income level) is tested and verified. The findings contribute to the system of knowledge on project complexity and provide guidelines for decision-makers to achieve a balance between project success and project management success in routine operation of construction projects.